Designing multi-aromatic ring epoxy composites to integrate high insulation and high heat resistance performances by electron-induced effect. (15th August 2022) - Zhang, Song; Chen, Weijiang; Zhao, Yushun; Ding, Lijian; Pan, Xiaofeng; Du, Bin; Shen, Hao; Gong, Chao; Yang, Wei; Yang, Kerong; Chen, Xin
Abstract: Multi-aromatic ring epoxy composites (MAREC) are prospective electronic packaging materials owing to their high heat resistance. However, the presence of numerous conjugated π bonds lead to poor insulation performance of MAREC, limiting its further application. Here, we propose a unique strategy to design MAREC to integrate high insulation and high heat resistance performances by electron-induced effect. The results show that the substitution of H atoms of benzidine by F atoms and –CF3 groups can lead to strong electron-induction effect. When all H atoms on the aromatic ring of benzidine are replaced by F atoms (8F), the electron-induced effect is the strongest (energy gap = 5.56 eV). The highest occupied molecular orbital of fluorenyl biphenyl exists by head to head overlap (similar to a σ bond), which significantly weakens the free sharing ability of the electrons on the conjugate π bonds of the aromatic ring. Although the reaction activity of –NH2 groups of 8F is low, the strong electron-induction effect of 8F can be fully harnessed by combining CF (two –CF3 groups replacing the H atoms of benzidine). The designed MAREC shows excellent insulation performance (AC breakdown strength = 39.18 kV/mm) and heat resistance performance ( T g = 234.5 °C, T d = 396.6 °C). Furthermore, the dielectric constant and dielectric loss are low (3.37@50Hz and 0.0035@50Hz, respectively). We successfully fabricated materials with enhanced insulation and heat resistance performances, which can be used as packaging materials for large-scale integrated circuits, new energy power equipment, and energy storage devices.